Tissue Depletion of Taurine Accelerates Skeletal Muscle Senescence and Leads to Early Death in Mice - Ito, Takashi (Public Library of Science, 2014)
Taurine (2-aminoethanesulfonic acid) is found in milimolar concentrations in mammalian tissues. One of its main functions is osmoregulation; however, it also exhibits cytoprotective activity by diminishing injury caused by stress and disease. Taurine depletion is associated with several defects, many of which are found in the aging animal, suggesting that taurine might exert anti-aging actions. Therefore, in the present study, we examined the hypothesis that taurine depletion accelerates aging by reducing longevity and accelerating aging-associated tissue damage. Tissue taurine depletion in taurine transporter knockout (TauTKO) mouse was found to shorten lifespan and accelerate skeletal muscle histological and functional defects, including an increase in central nuclei containing myotubes, a reduction in mitochondrial complex 1 activity and an induction in an aging biomarker, Cyclin-dependent kinase 4 inhibitor A (p16INK4a). Tissue taurine depletion also enhances unfolded protein response (UPR), which may be associated with an improvement in protein folding by taurine. Our data reveal that tissue taurine depletion affects longevity and cellular senescence; an effect possibly linked to a disturbance in protein folding.